2023
DOI: 10.2967/jnumed.122.265171
|View full text |Cite
|
Sign up to set email alerts
|

Site-Specifically Conjugated Single-Domain Antibody Successfully Identifies Glypican-3–Expressing Liver Cancer by Immuno-PET

Abstract: Primary liver cancer is the third leading cause of cancer-related deaths, and its incidence and mortality are increasing worldwide. Hepatocellular carcinoma (HCC) accounts for 80% of primary liver cancer cases. Glypican-3 (GPC3) is a heparan sulfate proteoglycan that histopathologically defines HCC and represents an attractive tumorselective marker for radiopharmaceutical imaging and therapy for this disease. Single-domain antibodies are a promising scaffold for imaging because of their favorable pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…Tumor-to-liver ratios by PET/CT and biodistribution analyses were notably higher than those reported by Natarajan et al using a similar 89 Zr-labeled human αGPC3 IgG antibody and Fayn et al using 89 Zr-labeled GPC3-targeting HN3 single-domain antibodies. In addition, there was a greater relative difference between tumor uptake and uptake in organs such as the heart, lungs, gastrointestinal tract, and kidneys on biodistribution analysis [16,17]. While different methods for model development and radioimmunoconjugate injection used may affect the results such that they are not directly comparable [16,17], it is possible that our humanized antibody has a higher speci city for GPC3-expressing tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor-to-liver ratios by PET/CT and biodistribution analyses were notably higher than those reported by Natarajan et al using a similar 89 Zr-labeled human αGPC3 IgG antibody and Fayn et al using 89 Zr-labeled GPC3-targeting HN3 single-domain antibodies. In addition, there was a greater relative difference between tumor uptake and uptake in organs such as the heart, lungs, gastrointestinal tract, and kidneys on biodistribution analysis [16,17]. While different methods for model development and radioimmunoconjugate injection used may affect the results such that they are not directly comparable [16,17], it is possible that our humanized antibody has a higher speci city for GPC3-expressing tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a greater relative difference between tumor uptake and uptake in organs such as the heart, lungs, gastrointestinal tract, and kidneys on biodistribution analysis [16,17]. While different methods for model development and radioimmunoconjugate injection used may affect the results such that they are not directly comparable [16,17], it is possible that our humanized antibody has a higher speci city for GPC3-expressing tumors. Furthermore, it should be noted that tumor-to-liver ratios were measured ve days after injection in this study compared with one to seven days after injection in the aforementioned studies, however our prior experiments with 89 Zr-αGPC3 M demonstrated high tumor-to-liver ratios calculated from four hours up to seven days after injection [6,11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32−34 As expected, the omission of the His tag markedly reduced the renal uptake of 68 Ga-NODAGA-SNA004-GSC, consistent with previous studies conducted by Yan Wang et al and Xavier et al 32−34 Concurrently, the reduction in the charge of the 68 Ga/chelator complex and the creation of structurally homogeneous site-specific molecular probes notably attenuated the hepatic uptake of 68 GA-NODAGA-SNA004-GSC, leading to PET images characterized by a heightened S/N ratio. 27,30,35,36 Trastuzumab and its associated ADC therapies represent well-established modalities for managing patients afflicted with HER2-positive BC. The downregulation of HER2 facilitated by trastuzumab and its associated ADCs during therapy serves as an early prognostic indicator of treatment efficacy.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Traditional bioconjugation approaches often yield heterogeneous tracer populations and may compromise their binding affinity and pharmacokinetic properties. These limitations can be mitigated by site-specific conjugation. Numerous studies focusing on tracers employing cysteine-based site-specificity have consistently demonstrated a higher signal-to-noise (S/N) ratio compared to those with random conjugation. , …”
Section: Introductionmentioning
confidence: 99%